Theoretical solution for multi-span continuous cable structures considering sliding. (15th December 2020) - Chen, Shizai; Yang, Menggang; Meng, Dongliang; Hu, Shangtao
Abstract: This paper proposes a theoretical solution for multi-span continuous sliding cable structures, which were usually analyzed by numerical simulations. Firstly, the analytical equation for the unstressed length of single-span cable based on the undeformed configuration is derived, in which the tension forces at the ends can be accurately calculated. Then, according to the tension balance condition at sliding joints and the assumption of invariant total unstressed cable length (ITUL method), multivariate transcendental equations for the sliding analysis of multi-span cable structures with and without considering friction are established and solved by multiple Newton-Raphson iterations. Moreover, a theoretical method based on the assumption of invariant total cable length (ITL method) is also proposed and the applicability of the ITL method is investigated. Finally, four typical examples are analyzed by the ITUL method, and the accuracy of the ITL method as well as some existing numerical simulations is evaluated. The result shows that the ITUL method proposed in this paper is more accurate and reliable than the ITL method. The ITUL method can provide a theoretical basis for the design and analysis of multi-span sliding cable structures.